The Use of Pragmatics and Discourse Analysis to Analyze George Orwell’s "Shooting an Elephant" 1936 - Touhami, Ibtissem; Saci, Othmane Ben Affane (Faculty of Letters and Foreign Languages Department of English, 2018)
The current dissertation undertakes an analytical research that aims at discerning The linguistic and political references in George Orwell’s "Shooting an elephant" 1936 . To fulfill this aim, this dissertation will also attempt to demonstrate that Orwell’s short story )essay(, which represents the British rule over India and Burma, embodies and reflects the author’s attempt to reject the dominant mode that the powerful countries had over the colonized countries during the colonial era. Thus, the current research seeks to investigate the author’s use of peculiar linguistic mechanisms as a means to make his personal anecdote proves to be an effective tool to reflect up on his own beliefs. As a short story, "Shooting an elephant" defies the typical perception of literature that gives importance only to lengthy pieces of writing; however, what this research argues is that Orwell uses his personal experience as a means to make it clear that his imperialism is evil. In this regard, an analytical approach is used in order to analyze the essay under the scope of discourse analysis and pragmatics